Parasitism by Chelonus blackburni (Hymenoptera) affects food consumption and development of Helicoverpa armigera (Lepidoptera) and cellular architecture of the midgut - Sanap, Yogita; Dawkar, Vishal V.; Giri, Ashok P.; Sen, Avalokiteswar; Pandit, Radhakrishna S. (Journal of Asia-Pacific Entomology, 2016)
Biological control agents are vital components of an integrated pest management strategy, and this is frequently referred to as natural control. Natural enemies of insect pests include predators, parasitoids, and pathogens. Among them, a parasitoid, Chelonus blackburni (Cameron), was found to be the best biological control agent for the polyphagous pest, Helicoverpa armigera (Hubner). C. blackburni alters the feeding performance of H. annigera larvae upon parasitism and as a result severely affects growth and development. Moreover, it shortens the feeding period of H. armigera and increases mortality. Furthermore, total hemocyte count (THC) was significantly decreased in parasitized larvae than control. Parasitized H. armigera had 26% less number of blood cells compared to healthy larvae. Histological studies showed that the structure of midgut of H. annigera is drastically affected by C. blackburni leading to reduced food consumption, which ultimately led to larval death. The present study provides an insight to changes involved in H. annigera due to parasitism by C blackburni, a parasite that could be used as an effective biocontrol agent to manage H. armigera. (C) 2015 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society. Published by Elsevier B.V. All rights reserved.